Hak Asasi Manusia dalam Politik Islam: Telaah Normatif Terhadap Prinsip dan Penerapannya - Wardani, Mufti (PT. Sharia Journal and Education Center, 2024)
Abstract ABSTRACT This research aims to critically examine the relationship between human rights and Islamic politics, focusing on a normative analysis of human rights principles in Islam and their application in a political context. The study employs a normative-analytical approach, involving an in-depth analysis of primary Islamic sources, including the Quran and Hadith, as well as relevant secondary literature on human rights and Islamic politics. Case studies of contemporary Muslim countries are conducted to provide practical perspectives on how human rights principles are applied within the context of Islamic politics. The significance of this research lies in its contribution to a more nuanced understanding of the relationship between human rights and Islam, which is crucial for academic purposes and practical implications in public policy, international relations, and interfaith dialogue. The article begins with a comprehensive literature review on the concepts of human rights and Islamic politics, followed by a discussion of human rights principles in Islam and an analysis of their application in historical and contemporary political contexts. The analysis highlights the congruence between principles and practices, as well as challenges in interpretation and implementation. The article concludes with theoretical and practical implications of the research findings and recommendations for future research and policy. Through this research, a deeper and more nuanced understanding of the position of human rights in Islamic politics is expected, contributing to a more constructive dialogue between Islamic traditions and global human rights discourse. Keywords: Human Rights, Political Islam, Principles, Implementation Abstrak Penelitian ini bertujuan untuk mengkaji secara kritis hubungan antara hak asasi manusia dan politik Islam, dengan fokus pada analisis normatif prinsip-prinsip hak asasi manusia dalam Islam dan penerapannya dalam konteks politik. Penelitian ini menggunakan pendekatan normatif-analitis, yang melibatkan analisis mendalam terhadap sumber-sumber utama Islam, termasuk Al-Quran dan Hadis, serta literatur sekunder yang relevan tentang hak asasi manusia dan politik Islam. Studi kasus negara-negara Muslim kontemporer dilakukan untuk memberikan perspektif praktis tentang bagaimana prinsip-prinsip hak asasi manusia diterapkan dalam konteks politik Islam. Signifikansi penelitian ini terletak pada kontribusinya terhadap pemahaman yang lebih bernuansa tentang hubungan antara hak asasi manusia dan Islam, yang sangat penting untuk tujuan akademis dan implikasi praktis dalam kebijakan publik, hubungan internasional, dan dialog antar agama. Artikel ini diawali dengan tinjauan literatur yang komprehensif mengenai konsep-konsep hak asasi manusia dan politik Islam, diikuti dengan diskusi mengenai prinsip-prinsip hak asasi manusia dalam Islam dan analisis mengenai penerapannya dalam konteks politik historis dan kontemporer. Analisis ini menyoroti kesesuaian antara prinsip-prinsip dan praktik-praktik, serta tantangan-tantangan dalam penafsiran dan implementasi. Artikel ini diakhiri dengan implikasi teoritis dan praktis dari temuan penelitian dan rekomendasi untuk penelitian dan kebijakan di masa depan. Melalui penelitian ini, diharapkan dapat diperoleh pemahaman yang lebih mendalam dan lebih bernuansa tentang posisi hak asasi manusia dalam politik Islam, yang dapat berkontribusi pada dialog yang lebih konstruktif antara tradisi Islam dan wacana hak asasi manusia global. Kata kunci: Hak Asasi Manusia, Politik Islam, Prinsip, Penerapan